Menilik Peran Jaksa dalam Pengentasan Persoalan Overcrowding di Indonesia - Saputro, Adery Ardhan; Weriansyah, Aditya (Syntax Corporation, 2025)
The overcrowding of inmates in correctional institutions has raised Indonesia's ranking as one of the top ten countries in the world that have problems related to overcrowding. At least we can examine this phenomenon from 2 (two) points of view, namely overcrowding as a logical consequence of the high number of cases that enter the court (overloaded) and the high number of cases sentenced to prison. This paper aims to analyze the role of the Prosecutor's Office in overcoming the problem of overcrowding. The research uses a doctrinal research method with a qualitative approach through literature studies and legal comparisons. The results of the study show that against the phenomenon of overcrowding, the Prosecutor's Office has a central role to screen cases that can enter the court stage through the implementation of criminal case settlement outside the court even though the current legal framework is very limited. In addition, the Prosecutor's Office also has a central role in determining changes in sentencing policies in order to popularize the criminal justice system through the imposition of the charges that are prepared.